Activation of the Mating Pheromone Response Pathway of Lentinula edodes by Synthetic Pheromones. Issue 4 (2nd October 2018) - Ha, Byeongsuk; Kim, Sinil; Kim, Minseek; Ro, Hyeon-Su
Abstract: Pheromone (PHB)-receptor (RCB) interaction in the mating pheromone response pathway of Lentinula edodes was investigated using synthetic PHBs. Functionality of the C-terminally carboxymethylated synthetic PHBs was demonstrated by concentration-dependent induction of a mating-related gene ( znf2 ) expression and by pseudoclamp formation in a monokaryotic strain S1-11 of L. edodes . Treatment with synthetic PHBs activated the expression of homeodomain genes ( HD s) residing in the A mating type locus, and of A -regulated genes, including znf2, clp1, and priA, as well as genes in the B mating type locus, including pheromone ( phb ) and receptor ( rcb ) genes. The synthetic PHBs failed to discriminate self from non-self RCBs. PHBs of the B4 mating type ( B4 PHBs) were able to activate the mating pheromone response pathway in both monokaryotic S1-11 and S1-13 strains, whose B mating types were B4 (self) and B12 (non-self), respectively. The same was true for B12 PHBs in the B4 (non-self) and B12 (self) mating types. The synthetic PHBs also promoted the mating of two monokaryotic strains carrying B4 -common incompatible mating types ( A5B4 × A1B4 ). However, the dikaryon generated by this process exhibited abnormally high content of hyphal branching and frequent clamp connections and, more importantly, was found to be genetically unstable due to overexpression of mating-related genes such as clp1 . Although synthetic PHBs were unable to discriminate self from non-self RCBs, they showed a higher affinity for non-self RCBs, through which the mating pheromone response pathway in non-self cells may be preferentially activated.